2022
DOI: 10.3390/molecules27154833
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Composition and Biological Activities of Hedychium coccineum Buch.-Ham. ex Sm. Essential Oils from Kumaun Hills of Uttarakhand

Abstract: Hedychium coccineum Buch. Ham. ex Sm. is a perennial rhizomatous herb belonging to the family Zingiberaceae. The aim of the present study was to compare the chemical composition and biological activities of H. coccineum rhizome essential oil (HCCRO) and H. coccineum aerial part essential oil (HCCAO). The plant material was subjected to hydro-distillation using Clevenger’s apparatus in order to obtain volatile oil and analyzed for its chemical constituents using GC-MS. The comparative study of the rhizome and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 46 publications
0
10
1
Order By: Relevance
“…In this study, the percent composition of 1,8-cineole is higher in H. spicatum than in EO of Artemisia maritima and M. piperita [ 9 , 21 ]. Similarly, the composition of 1,8-cineole is lesser (12.2–23.15%) in H. spicatum oil [ 28 , 29 , 30 ] than in the current results. The composition of asarone in the present study is higher than in earlier reports, which observed comparatively less (9.5 – 50.09%) [ 31 , 32 ].…”
Section: Discussioncontrasting
confidence: 57%
“…In this study, the percent composition of 1,8-cineole is higher in H. spicatum than in EO of Artemisia maritima and M. piperita [ 9 , 21 ]. Similarly, the composition of 1,8-cineole is lesser (12.2–23.15%) in H. spicatum oil [ 28 , 29 , 30 ] than in the current results. The composition of asarone in the present study is higher than in earlier reports, which observed comparatively less (9.5 – 50.09%) [ 31 , 32 ].…”
Section: Discussioncontrasting
confidence: 57%
“…α‐Pinene displayed diverse biological activities (cytotoxicity, antiulcerogenic, antiosteoarthritis and gastroprotective effects) while β‐pinene exhibited cytotoxic and antibacterial effects [41] . p‐ Cymene and spathulenol widely utilized as antioxidant, antinociceptive, anti‐inflammatory, anxiolytic, anticancer, antiproliferative and antimicrobial activities [46,47] …”
Section: Resultsmentioning
confidence: 99%
“…[41] p-Cymene and spathulenol widely utilized as antioxidant, antinociceptive, anti-inflammatory, anxiolytic, anticancer, antiproliferative and antimicrobial activities. [46,47]…”
Section: Chemical Compositionmentioning
confidence: 99%
“…The leaf dip method was used to assess the insecticidal activity of GSAO and GSRO using the standard protocols [ 25 , 26 ].…”
Section: Methodsmentioning
confidence: 99%